POLITISASI BIROKRASI PENATAAN KINERJA PEGAWAI NEGERI SIPIL DI LINGKUNGAN PEMERINTAH DAERAH KABUPATEN INDRAGIRI HULU TAHUN 2012- 2014 - R.Rona Monika; Baskoro Wicaksono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Mutations in general ia an activity of employees from one agency to another agency with the objective to improve the efficient and effectiveness of the organization concerned. Basic foundation has been listed in the mutation process Peraturan Pemerintah Nomor 63 Tahun 2009 about Wewenang Pengangkatan, Pemindahan, dan Pemberhentian Pegawai Negeri Sipil. And in the decision Badan Kepegawaian Daerah Nomor 70/KEP/2003 about Pendelegasian Wewenang Kepala Kantor Regional Badan Kepegawaian Negara for Menetapkan Surat Keputusan and Persetujuan about Mutasi Kepegawaian Negeri Sipil. Activities aimed mutation as a form of refreshment functions and duties. There are 4 systems on which to base the implementation of personnel transfers that: (1) Merit System, (2) Seniority System, (3) Spoil System, (4) Nepotism System.Thus study was conducted in order to determine the politicization of the bureaucracy over the lot and routine tansfer of civil servants of local government environment Kabupaten Indragiri Hulu. Location of this research is conducted in Badan Kepegawaian Daerah and Regent’s office Kabupaten Indragiri Hulu. This type of research is qualitative research with descriptive methods. This study has shown that the policization of the bureaucracy that occured in the transfer of civil servants of local government envionment Kabupaten Indragiri Hulu is on the basic spoil system, not supposed to be that merit system.Keywords: Mutation, Government Employees, The Implementation Of The Basic Reasons Mutation